Über die Existenz von invarianten Finslerschen Metriken in homogenen Räumen - Jonušauskas, A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Ионушаускас. О существовании инвариантных финслеровых метрик в однородных пространствах A. Jonušauskas. Apie invariantinių Finslerio metrikų egzistenciją homogeninėse erdvėse